Globalization, infrastructure, and inclusive growth - L. Alan Winters (Asian Development Bank Institute (ADBI), 2014)
This paper covers threes issues: first, defining and measuring inclusive growth; second, the relationship between international trade and inequality; and third, the links between infrastructure and inequality. Both international trade and infrastructure make it easier for people to exchange goods and services and to increase income by allowing specialization, economies of scale, variety, etc. The gains are important not only in aggregate, but also at an individual level, and different people's ability to take advantage of them varies. Hence each can increase inequality. Critical to sharing the gains from trade is mobility - specifically labor mobility, which determines the capacity of people to move from areas, sectors, skills, or firms of low or declining opportunity to those of higher opportunity. In the context of inclusive growth, this constitutes a challenge. However, the answer should not be to eschew opening up the economy or building infrastructure, but to do so in an informed way and seek to undertake complementary policies that help the less well-off take advantage of them.
Keywords: F16; F64; H54; 330; trade; infrastructure; inequality; labor mobility; trade opening; globalization